Family Member Incarceration, Psychological Stress, and Subclinical Cardiovascular Disease in Mexican Women (2012–2016) - Connors, Kaela (Am J Public Health, 2020)
Objectives. To examine the association between family member incarceration, psychological stress, and subclinical cardiovascular disease (CVD). Methods. Between 2012 and 2016, 1849 CVD-free women from the Mexican Teachers’ Cohort responded to questions on family incarceration from the Life Stressor Checklist. Perceived stress and hair cortisol levels were measured in a subset of participants. Carotid intima-media thickness was measured, and carotid atherosclerosis was determined in all participants. We used multivariable quantile, linear, and logistic regression models to evaluate the association between family member incarceration, stress, and subclinical CVD. Results. Among women with a mean age of 49.7 years (SD ±5.2), 15.3% reported family member incarceration. We found that both perceived stress and hair cortisol levels were significantly higher in women with an incarcerated family member relative to women without one. After multivariable adjustment, women who reported family member incarceration had 41% (95% confidence interval = 1.04, 2.00) higher odds of carotid atherosclerosis compared with those who did not. Conclusions. Family member incarceration was associated with robust markers of stress and cardiovascular risk. Mass incarceration may have a long-lasting impact on physical health of affected families.